The Impact of Pillar II Funding: Validation from a Modelling and Evaluation Perspective. (17th November 2014) - Schroeder, Lilli Aline; Gocht, Alexander; Britz, Wolfgang
Abstract: We extend the Common Agricultural Policy Regionalised Impact Modelling System (CAPRI) with a regional computational general equilibrium (CGE) model to estimate the effects of the Pillar II of the Common Agricultural Policy. Our aim is to assess the modeling approach by comparing the scenario results with observations from the evaluation reports for rural development, supplemented with expert interviews and findings from the literature. For this purpose, an ex‐post scenario is developed for Germany that models the effect of the Pillar II measures in 2006. We observe a moderate impact, namely, an increase in agricultural income (5%) and agricultural land use (0.15%), particularly grassland, and a substitution of arable land with grassland. This effect leads to a total increase in agricultural production, particularly of beef, and to an increase in total greenhouse gas emissions and total nitrogen surplus for Germany. Greenhouse gas emissions and nutrient surpluses per ha, however, are reduced. We observe that farm investment programmes displace private investment. The evaluation reports confirm the moderate impact and our major results, as does the comparison with other literature. However, the conclusions about agri‐environment measures and their impact on income differ. The most important difference between our results and the evaluation reports and majority of the present literature is that we also quantify the joint effect between the whole economy and policy measures, with some contradictory effects.